Liaison des idées et variété des esprits : de Malebranche à l’empirisme des Lumières - André Charrak (Astérion)
Condillac’s indebtment to Locke is often stressed, especially regarding the association of ideas; yet, one should also recall the importance of Malebranche in the elaboration of Condillac’s philosophy. Nevertheless, the takeover of Malebranche by Condillac, once purified of psychophysical hypotheses on the soul/body union, has to find new tools in order to explain the phenomenon of the variety of spirits, wich Descartes and Malebranche could easily explain in the context of the union, in particular by a reference to the variety of bodies and of corporal events. The focus of this contribution is therefore the tension between the generality and the unity of the laws of associations of ideas on the one hand, the modalities of their particularization in different spirits on the other hand.